Multichannel bio-impedance spectroscopy system on FPGA - Al-Hashimi, Ahmed Rabeea Abdulhameed (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
This work presents the design and implementation of a multichannel bio-impedance spectroscopy system on FPGA (Field Programmable Gate Array). It aims to introduce a design that is capable of acquiring multiple signals from multiple bio-impedance sensors, process the data on the FPGA and store the final data in the memory. The system employs the Digital Automatic Balance Bridge (DABB) method to acquire data from bio-impedance sensors. The DABB measures initial data of a known impedance to extrapolate the value of the impedance for the device under test. This method offers a simpler design because the balancing of the circuit is done digitally in the FPGA rather than using an external circuit. Calculations of the impedance values for the device under test were done in the designed processor. The final data is sent to an onboard flash memory to be stored for later access. The control unit handles the interfacing and scheduling between these different modules (processor and flash memory) as well as interfacing to multiple balance bridge circuits and multiple biosensors. The system has been simulated successfully with acceptable performance compared to other FPGA based solutions, and showed a robust design in terms of multichannel acquisition ability and the accuracy in the selected frequency range. The system is capable of interfacing with multiple bio-sensors, processing data and storing it in a flash memory. The system uses a small amount of the resources on the FPGA chip.